The SKA3-DUSP2 Axis Promotes Gastric Cancer Tumorigenesis and Epithelial-Mesenchymal Transition by Activating the MAPK/ERK Pathway - Zhang, Chao; Zhao, Shutao; Tan, Yuen; Pan, Siwei; An, Wen; Chen, Qingchuan; Wang, Xudong; Xu, Huimian (Frontiers in Pharmacology, 2022)
Background: Spindle and kinetochore-related complex subunit 3 (SKA3), a member of the SKA family of proteins, is associated with the progression of multiple cancers. However, the role of SKA3 in gastric cancer has not been studied. Methods: The expression levels of SKA3 and dual-specificity phosphatase 2 (DUSP2) proteins were detected by immunohistochemistry. The effects of SKA3 and DUSP2 on the proliferation, migration, invasion, adhesion, and epithelial-mesenchymal transition of gastric cancer were studied in vitro and in vivo. Results: Immunohistochemical analysis of 164 cases of gastric cancer revealed that high expression of SKA3 was negatively correlated with DUSP2 expression and related to N stage, peritoneal metastasis, and poor prognosis. In vitro studies showed that silencing SKA3 expression inhibited the proliferation, migration, invasion, adhesion and epithelial-mesenchymal transition of gastric cancer. In vivo experiments showed that silencing SKA3 inhibited tumor growth and peritoneal metastasis. Mechanistically, SKA3 negative regulates the tumor suppressor DUSP2 and activates the MAPK/ERK pathway to promote gastric cancer. Conclusion: Our results indicate that the SKA3-DUSP2-ERK1/2 axis is involved in the regulation of gastric cancer progression, and SKA3 is a potential therapeutic target for gastric cancer.